凸轮机构六次多项式运动规律的理论分析 - 赖晓桦 (Jixie chuandong)
The advantages of theoretical analysis by using the sextic polynomial for the motion of cam-follower mechanism are presented.Compared to the motions in other polynomial models,in the sextic polynomial,there are not rigid impact in the linear equation and soft impact in the quadratic equation,respectively,but there is the advantage of the quintic polynomial.With the sextic polynomial model,the forces on the cam and power fluctuations can be improved by adjusting the parameter derived.